Five-year clinical performance of monolithic and partially veneered zirconia single crowns: a prospective observational study - Waldecker, Moritz; Behnisch, Rouven; Rammelsberg, Peter; Bömicke, Wolfgang (Journal of prosthodontic research, 2022)
Purpose: The purpose of this study was to prospectively evaluate the medium-term clinical performance and esthetics of monolithic and partially (i.e., facially) veneered zirconia single crowns (MZ-SC and PZ-SC, respectively).Methods: Between September 2011 and June 2013, 68 participants received 90 MZ-SC and 72 PZ-SC. Clinical study documentation was performed at crown cementation (baseline), at 6-month follow-up, and then yearly thereafter using standardized report forms. Three participants with four MZ-SC dropped out during clinical follow-up. Thus, 65 participants (n = 31, 47.7% men) fitted with 158 restorations (86 MZ-SC, 72 PZ-SC) were evaluated. The mean observation period of the restorations was 5.8 ±2.5 years; 6.3 ±2.2 for MZ-SC and 5.2 ±2.6 for PZ-SC.Results: The 5-year rate of complication-free survival (success) was 87.0% for MZ-SC and 95.8% for PZ-SC (log-rank test, p = 0.026). The 5-year failure-free survival rate was 93.1% for MZ-SC and 96.2% for PZ-SC (log-rank test, p = 0.111), and the 5-year ceramic fracture-free survival rate was 100% for MZ-SC and 98.6% for PZ-SC (log-rank test, p = 0.274). Crowns of both designs were awarded excellent scores for esthetics by participants and dentists.Conclusion: Monolithic and partially veneered zirconia crowns can be used clinically with high medium-term survival and success and uncompromised esthetic results.
Gesehen am 21.12.2022